KONSEKUENSI ADOPSI PENUH IFRS TERHADAP PELAPORAN KEUANGAN DI INDONESIA - Immanuela, Intan (Universitas Katolik Widya Mandala Surabaya Kampus Kota Madiun, 2012)
International Financial Reporting (IFRS)is the global international standards for business operation and security market. Indonesia as a member of forum G20 must use fair value concept to measure and disclosure the financial report. Fair Value is the price that would be received to sell an asset or paid to transfer a liability in an orderly transaction between market participants at the measurement date. Fair value changes measurement and financial reporting in Indonesia which used historical cost. Fair value concept have several advantages and disadvantages. Fair value concept makes Indonesia financial report more comparable.